Advances in Human Factors in Cybersecurity Proceedings of the AHFE 2018 International Conference on Human Factors in Cybersecurity, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Ahram, Tareq Z.; Nicholson, Denise (Advances in Intelligent Systems and Computing, 2019)
This book reports on the latest research and developments in the field of cybersecurity, particularly focusing on personal security and new methods for reducing human error and increasing cyber awareness, as well as innovative solutions for increasing the security of advanced Information Technology (IT) infrastructures. It covers a broad range of topics, including methods for human training; novel cyber-physical and process-control systems; social, economic, and behavioral aspects of cyberspace; issues concerning the cybersecurity index; security metrics for enterprises; and risk evaluation. Based on the AHFE 2018 International Conference on Human Factors in Cybersecurity, held on July 21-25, 2018, in Orlando, Florida, USA, the book not only presents innovative cybersecurity technologies, but also discusses emerging threats, current gaps in the available systems, and future challenges that can be successfully overcome with the help of human factors research.